The Influence of Entrepreneurial Literacy, Entrepreneurial Behavior and Market Orientation Towards Sustainability of Halal Food MSMEs In East Medan District - Purba, Siti Khoiriyah; Dahrani (Jurnal Manajemen Bisnis, 2026)
This study examines the effect of entrepreneurial literacy, entrepreneurial behavior, and market orientation on the sustainability of halal food MSMEs in Medan Timur District. This issue is important due to increasing competition, limited managerial skills, and low market adaptability. This research used a quantitative approach with a survey method. Data were collected through online questionnaires from 86 MSME actors selected from a population of 600 businesses. Data analysis was conducted using multiple linear regression with SPSS. The results indicate that entrepreneurial literacy, entrepreneurial behavior, and market orientation have positive and significant effects on MSME sustainability, both partially and simultaneously. These variables explain 81.2% of the variance in sustainability, while 18.8% is influenced by other factors. Market orientation has the strongest effect, highlighting the importance of understanding customer needs and market trends. Therefore, improving these aspects is essential to support sustainable MSME development.